Issues of implementing system integration in an oganizations through system integrator perspective / Awang Saad Awang Salleh - Awang Salleh, Awang Saad (2010)
Organizations often have information systems belonging to different computer generations. These systems contain much valuable data to the organizations concerned. However, these systems are often unable to communicate with each other, due to incompatibilities. Moreover, replacing these systems with new systems is also very costly. Therefore the latest trend is integrating the existing systems with each other with the help of different system integration technologies. Among organizations especially in government sector, it is increasingly common to outsource their Information System (IS) especially System Integration (SI) to avendor which is System Integrator. When the organization information systems are integrated with new technology they bring about various effects and issue to the system integrator and organizations itself in concern. This paper will be an exploratory study of the architecture approach and architecture adopted by Xy base as a system integrator in implementing system integration for various organizations and also to find the issues / barriers which are the actual problems of implementation being faced. Understanding the issues is paramount to select the correct solution and the overall success of system integration implementation. The result shall be beneficial as it will serve as guidelines and considerations for both system integrators and organizations itself in successfully embark in system integration effort.